La pareja, ¿fundamento de la sociedad ? Dualismo jerárquico y relaciones de género en comunidades rurales de la Sierra de Ancash, Perú - Sofía Venturoli (Nuevo mundo - Mundos Nuevos, 2012)
We present an ethnographic case from the highlands area of Ancash Department, Peru, addressing the issue of gender relations as expressing implicit and explicit hierarchical dualism where one part has dominance over the other. The Andean dualism, which is explained and depicted in many different areas of social and symbolic practices in the Andes, seems to include a hierarchy often expressed on the basis of gender concepts and reproduced in the daily life of rural communities.